The Nullity is a Threat to The Survival and Continuity of Commercial Companies - Lounnas, Donia; Belaissaoui, Mohamed Tahar (Journal of Legal Studies and Researches, 2022)
It poses a danger to commercial companies in the stage of their establishment, and the Algerian legislator has acted turning, into a will that takes measures to protect commercial companies at some stage that they verify, and thus limit the danger of his will, which carries with it mechanisms that reflect the legislator’s sincere, will but the protection permeated many of loopholes and shortcomings.